Assessment of Seasonal Dynamicity of Herbaceous Plant Diversity, Phytosociology and Composition in Narmada Canal Command Area of Kachchh District, Gujarat - Yadav, Rajkumar; Tatu, Ketan; Suthar , Ashok; Sugoor, R.K. (Annals of Arid Zone, 2023)
The seasonal phytosociological study in Narmada Canal Command (NCC)area of Kachchh district has revealed that there is seasonal variation in the herbaceousplant diversity. The qualitative assessment has shown that in the pre-monsoon season,165 herbaceous plant species existed in the NCC area in Kachchh. On other hand,during post-monsoon season a total of 255 herbaceous species were recorded. Thecurrent study has reflected that, the Kachchh NCC area supports some locally rare oroccasional plant species of Gujarat State. Values of density, frequency, abundance andspecies composition of herbaceous plants were in the range of 16133.33 ind. ha -1 to 66.67ind. ha -1 , 32.00% to 0.67%, 10.70 ind. quadrat -1 m -2 to 1.0 ind. quadrat -1 m -2 and 16.85%to 0.07%, respectively during the pre-monsoon season while during the post-monsoonseason the corresponding values were in the range of 34133.33 ind. ha -1 to 200 ind. ha -1 ,60.00 % to 1.33 %, 7.73 ind. quadrat -1 m -2 to 1.50 ind. quadrat -1 m -2 and 11.57% to 0.07%,respectively. In this study, the Simpson Diversity Index was higher (i.e. 0.97) in post-monsoon season as compared to that in pre-monsoon season (i.e. 0.93) indicating thatthe diversity was good in post-monsoon season. The study revealed that the seasonaldynamicity of herbaceous vegetation may be due to the availability of good habitat inthe arid or semi-arid area of NCC